Stranger intimacy : contesting race, sexuality, and the law in the North American West - Shah, Nayan, 1966- (American crossroads, 2011)
"In exploring an array of intimacies between global migrants Shah illuminates a stunning, transient world of heterogeneous social relations--dignified, collaborative, and illicit. At the same time he demonstrates how the United States and Canada, in collusion with each other, actively sought to exclude and dispossess nonwhite races. Stranger Intimacy reveals the intersections between capitalism, the state's treatment of immigrants, sexual citizenship, and racism in the first half of the twentieth century"--Provided by publisher.